Work Methods for Packaging Line for the Butterfly Extension Dining Set at Latitude Treefurniture Sdn. Bhd. - H’ng, Jia Yun (2015)
The project is intended to improve the current work method for packaging line for the butterfly extension dining set at Latitude Tree Furniture Sdn. Bhd by using DMAIC approach. The weakness of current packaging line is studied and problem of packaging line is identified, which is uneven distribution of task among stations. Few solutions to the problem arc proposed such as rearrangement of tasks and other improvement methods in SS. The result of improvement is tested out using Arena simulating software.